Micro-PET imaging of hepatitis C virus NS3/4A protease activity using a protease-activatable retention probe - Chuang, Chih-Hung; Cheng, Tian-Lu; Chen, Wei-Chun; Huang, Yi-Jung; Wang, Hsin-Ell; Lo, Yen-Chen; Hsieh, Yuan-Chin; Lin, Wen-Wei; Hsieh, Ya-Ju; Ke, Chien-Chih; Huang, Kang-Chieh; Lee, Jin-Ching; et al. (Frontiers in Microbiology, 2022)
Hepatitis C virus (HCV) NS3/4A protease is an attractive target for direct-acting antiviral agents. Real-time tracking of the NS3/4A protease distribution and activity is useful for clinical diagnosis and disease management. However, no approach has been developed that can systemically detect NS3/4A protease activity or distribution. We designed a protease-activatable retention probe for tracking HCV NS3/4A protease activity via positron emission topography (PET) imaging. A cell-penetrating probe was designed that consisted of a cell-penetrating Tat peptide, HCV NS3/4A protease substrate, and a hydrophilic domain. The probe was labeled by fluorescein isothiocyanate (FITC) and 124I in the hydrophilic domain to form a TAT-ΔNS3/4A-124I-FITC probe. Upon cleavage at NS3/4A substrate, the non-penetrating hydrophilic domain is released and accumulated in the cytoplasm allowing PET or optical imaging. The TAT-ΔNS3/4A-FITC probe selectively accumulated in NS3/4A-expressing HCC36 (NS3/4A-HCC36) cells/tumors and HCV-infected HCC36 cells. PET imaging showed that the TAT-ΔNS3/4A-124I-FITC probe selectively accumulated in the NS3/4A-HCC36 xenograft tumors and liver-implanted NS3/4A-HCC36 tumors, but not in the control HCC36 tumors. The TAT-ΔNS3/4A-124I-FITC probe can be used to represent NS3/4 protease activity and distribution via a clinical PET imaging system allowing. This strategy may be extended to detect any cellular protease activity for optimization the protease-based therapies.